2019
DOI: 10.1111/ldrp.12203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computerized Instruction on the Use of Punctuation Strategies by Students with LD

Abstract: An interactive multimedia software program was developed for teaching punctuation strategies and then tested with middle‐school and high‐school students with learning disabilities. Students at each school level were randomly selected into an experimental or control group. Results showed that experimental students at both school levels performed similarly by earning significantly higher scores on a test of punctuation usage than the control students. Additionally, experimental students in both school cohorts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Clearly, the multimedia instruction represented here and in other studies (e.g., Lancaster et al, 2002, 2006, 2009; Schumaker, Fisher, & Walsh, 2019; Schumaker, Walsh, & Fisher, 2019) is a different type of instruction than what is typically used in today’s schools. Classrooms need to be equipped with computers that can run these very interactive programs (Lancaster et al, 2005, 2007; Schumaker, 2013; Schumaker & Sheldon, 2009, 2010), as well as with printers that students can use to print out their products. Nevertheless, interactive programs are required since students need high levels of interactivity and feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the multimedia instruction represented here and in other studies (e.g., Lancaster et al, 2002, 2006, 2009; Schumaker, Fisher, & Walsh, 2019; Schumaker, Walsh, & Fisher, 2019) is a different type of instruction than what is typically used in today’s schools. Classrooms need to be equipped with computers that can run these very interactive programs (Lancaster et al, 2005, 2007; Schumaker, 2013; Schumaker & Sheldon, 2009, 2010), as well as with printers that students can use to print out their products. Nevertheless, interactive programs are required since students need high levels of interactivity and feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have developed and tested some IM programs for teaching writing strategies. For example, Schumaker, Fisher, & Walsh (2019) tested an IM program for teaching Punctuation Strategies (Schumaker & Sheldon, 2010), and Schumaker, Walsh, & Fisher (2019) tested a similar program for teaching Commas Strategies (Schumaker & Sheldon, 2009). The instructional methodology used in both IM programs was Strategic Instruction (Ellis et al, 1991; Schumaker & Deshler, 2006).…”
mentioning
confidence: 99%
“…Some researchers have shown that these instructional methods can be incorporated into interactive multimedia (IM) programs to teach academic skills (e.g., Lancaster et al, 2006Lancaster et al, , 2009Schumaker, 2020;Schumaker et al, 2019aSchumaker et al, , 2019b) and social skills. With regard to social skills, Lancaster et al (2002) conducted a study whereby students with learning disabilities (LD) were taught self-advocacy skills to be used in Individualized Education Program (IEP) meetings with an IM program.…”
Section: Multimedia Instruction As a Solutionmentioning
confidence: 99%